Efektivitas Metode Ummi Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Pada Kelas Ibu-Ibu Di Rumah Tahfidz Haromain - Dariyanto Dariyanto; Fitri Amalia Majid Dariyanto; Itsna Rusydiana Dariyanto; Binti Mar’atus Sholihah Dariyanto; Yuliana Nurul Islami Dariyanto (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study investigates the effectiveness of the Ummi Method in improving Qur’an reading skills among mothers attending classes at Rumah Tahfidz Haromain. The research background highlights the challenges faced by adult learners, particularly low fluency, inaccurate articulation of makhraj, and inconsistent application of tajwid. The Ummi Method was selected due to its structured approach, emphasis on tartil habituation, and integration of both classical and individualized strategies. Employing a quantitative approach with a one-group pretest–posttest design, the study involved 20 purposively selected participants. Data collection instruments included pre- and post-intervention reading tests, alongside observation sheets assessing participation and motivation. Data analysis utilized paired sample t-tests and descriptive statistics. Findings indicate a significant improvement, with posttest scores showing a 25% increase compared to pretest results. Enhancements were observed across fluency, makhraj accuracy, and consistent tajwid application. Qualitative data further revealed heightened motivation, active participation, and increased self-confidence among participants. These outcomes were supported by talaqqi, repetitive practice (tikrar), and personalized correction. The results demonstrate that the Ummi Method is effective not only for children but also adaptable for adult learners in nonformal institutions. The study recommends sustained implementation supported by relevant media and certified instructors to optimize long-term outcomes